An overview of liberation theology in orthodox Russia - Negrov, Aleksandr I. (HTS teologiese studies, 2005)
The aim of this article is to demonstrate the presence of a theological system of socio-critical and socio-pragmatic strands within Russian Christianity at the beginning of the twentieth century. The political and social situation in Russia at that time was reflected in a reading of the New Testament that went far beyond the more customary ecclesiastic, dogmatic and ethical issues that had traditionally concerned Russian Orthodox theology. Among the Orthodox thinkers there were two camps that focused on anti-oppression issues. Some combined these issues with the liberationist ideology of the Russian Marxists and Socialists; while the other regarded these liberation movements as an anti-Christian way of interpreting Christianity. This article further claims that certain modern developments in Liberation Theology can be found in the period during which the Russian religious thinkers attempted to develop a theological perspective which paid attention to the social and political dimensions inherent in social democracy (Marxism).